2021
DOI: 10.3390/nu13020480
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Renin–Angiotensin System and Lipid Metabolism: Effects of Virgin Olive Oil versus Butter in the Diet

Abstract: The brain renin–angiotensin system (RAS) has been recently involved in the homeostatic regulation of energy. Our goal was to analyse the influence of a diet rich in saturated fatty acids (butter) against one enriched in monounsaturated fatty acids (olive oil) on hypothalamic RAS, and their relationship with the metabolism of fatty acids. Increases in body weight and visceral fat, together with an increase in aminopeptidase A expression and reductions in AngII and AngIV were observed in the hypothalamus of anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…As indicated previously, the source of fat in the diet has demonstrated to be decisive in the development of metabolic syndrome, obesity and hypertension [62][63][64]. Changes in systemic and local RAS play an important role in this process [4,5,15,65,66]. The increase in the blood pressure values results in an increase of the renal artery pressure, triggering a high rate of filtration and increasing the delivery of sodium and water to the distal nephron, where the macula densa is located [67].…”
Section: Discussionmentioning
confidence: 99%
“…As indicated previously, the source of fat in the diet has demonstrated to be decisive in the development of metabolic syndrome, obesity and hypertension [62][63][64]. Changes in systemic and local RAS play an important role in this process [4,5,15,65,66]. The increase in the blood pressure values results in an increase of the renal artery pressure, triggering a high rate of filtration and increasing the delivery of sodium and water to the distal nephron, where the macula densa is located [67].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, it was observed in the ventricle that CysAP (mb) activity was significantly elevated with diet S in addition to VOO. These data may have repercussions with previously published data, where they identified that the local and serum mRNA and/or the activities of AspAP and GluAP progressively increase with the degree of saturation of fatty acids in the diet [ 4 , 7 , 10 , 72 ]. GluAP activity is modified by the composition of fatty acids in the diet and by the cholesterol content [ 4 , 5 , 6 , 9 , 57 ], directly or indirectly, and with an important role in the development of cardiovascular disorders and the pathophysiology of hypertension.…”
Section: Discussionmentioning
confidence: 61%
“…[4,7,9]. Elevated plasma cholesterol levels are another important risk factor widely recognized for its relationship with angiotensin metabolism [4,5,7,10,12,72], with Mediterranean countries showing lower rates of heart disease than other countries due to the usual diet rich in olive oil [75].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations